A GIS-Based Streets Network Analysis in Al-Riyadh District, Al-Khartoum City - Abdelrahman, Sahar Ismail Mohieldin (Journal of engineering sciences and information technology, 2023)
In light of the remarkable development and high population density, there are many questions regarding traffic problems and the possibility of reaching the event location in the shortest time. For all these inquiries, this paper aims to analyze the streets network of Al Riyadh district using Geographic Information Systems (GIS), represented in finding the optimal path between the home and the school based on time and length and finding another path in the event of an obstacle in the chosen path, clarifying the service area for an ambulance center, and also knowing the closest fire station to the place of the fire and the optimal path between them. To achieve these objectives, an ArcGIS 10.6 program was used, and many procedures were taken, a geographical database was created, a network dataset was built, and a lot of analyses were done by the network analyst toolbar. According to the findings of this study, was known the optimal path between two locations, the service area of an ambulance center and the closest fire station to the fireplace, to be able to perform the required service in the shortest possible time. This work is a real contribution to the development of societies, as it is difficult to reach these results without using the capabilities of GIS. Therefore, it is recommended to implement all the analysis tools for the streets network within the GIS program.